From Beat to Bit: Open Music Production in the Underground Scene - Sousa, Júlio César de; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação Musical, 2025)
The democratization of technology has made independent music production increasingly accessible. However, the early stages of this journey are often marked by difficulties and disorientation, due to the complexity of the processes involved—from ideation to distribution. Proprietary DAWs (Digital Audio Workstations) such as FL Studio and Ableton Live, while widely known and used in digital audio production, present financial barriers due to their paid licensing models. In contrast, free and opensource DAWs like LMMS (Linux MultiMedia Studio) offer significant potential to support independent artists. Their open project formats allow for transparency, adaptability, and the integration of programming logic and musical theory to automate early creative processes. This research aims to analyze file types generated by open-source DAWs and to develop functional tools to support learning and creation in music production, especially within underground or independent scenes. The manipulation of project files through scripts or web interfaces can facilitate project generation based on genres, BPM, or sonic references— enhancing the workflow and creative autonomy of emerging artists.